Modulation techniques to reduce leakage current in three-phase transformerless H7 photovoltaic inverter - Freddy, T.K.S.; Rahim, N.A.; Hew, W.P.; Che, H.S. (Institute of Electrical and Electronics Engineers (IEEE), 2015)
Recently, reduced common-mode voltage (CMV) pulsewidth modulation (RCMV-PWM) methods have been proposed to reduce the leakage current in three-phase transformerless photovoltaic (PV) systems. However, most of these studies only focus on leakage current elimination and neglect the overall performance of the PV systems on issues such as cost, voltage linearity, dc-link current ripples, and harmonic distortion. In this paper, a three-phase transformerless inverter, adapted from the single-phase H5 topology, is investigated. Since the H5 topology has been conventionally developed for a single-phase system, its adaptation to the three-phase system requires the development of corresponding three-phase modulation techniques. Hence, modulation techniques are proposed based on conventional PWM. The performances of the proposed PWM, in terms of CMV, leakage current, voltage linearity, output current ripples, dc-link current ripples, and harmonic distortion are studied and discussed via simulation and experiment. It is proven that the proposed topology is able reduce the leakage current without sacrificing the overall performance of the system.